Minimum Authorized Capital After the Enactment of Job Creation Law - Wiryadi, Kania Jennifer; Novendra, Bayu (University of Jember, 2021)
In a limited liability company, capital becomes one of the primary elements. However, the regulation regarding capital in Indonesia has changed several times, as its latest concern on the enactment of the omnibus bill on Job Creation Law in 2020. This paper discussed the following problems. First, what are the status quo and the development of regulations regarding minimum capital requirements in Indonesia? Second, what are the pros and cons of minimum capital requirement regulations and their developments in other countries? Third, what is the minimum capital requirements regulation that suits the conditions in Indonesia? This paper used legal research, emphasizing literature study. In so doing, the data were analyzed with the deductive method to construct conclusions. This paper showed that each limited liability company from the 1995 Limited Company Law, the 2007 Limited Company Law to the Job Creation Law had various minimum capital requirements provisions that lasted to its abolishment under the Job Creation Law. In this context, the initial policy on the minimum capital requirement was to protect creditors. In practice, however, this policy was not effective because of many other effective alternatives to protect creditors, by encouraging transparency in corporate transactions and offering easy access to corporate information. The dominance of micro and small business units in Indonesia (99% of business units) explained the urgency of eliminating minimum capital requirements regulations. The elimination of minimum authorized capital requirements was a tremendous effort to strengthen micro and small enterprises. KEYWORDS: Limited Liability Company, Job Creation Law, Company Law.